SINTESIS KALKON PIRIDIN DAN TURUNANNYA DARI ASETILPIRIDIN DAN INDOL-3-KARBALDEHID SERTA UJI AKTIVITASNYA SEBAGAI ANTIOKSIDAN - Juwita Oktavani; Hilwan Yuda Teruna; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
In this research, chalcones  of  acetylpyridine  derivatives  were synthesized  using stirrer method  with  a  base catalyst  (NaOH)  at room temperature. The compound  produced from the  synthesis  was  (E)-3-(1H-indole-3-yl)-1-(pyridine-3-yl)prop-2-en-1-one  (1).  The synthesized compound was  characterized using UV,  IR, NMR and Mass  Spectroscopy.  Its antioxidant activity was tested using DPPH method which  compound  (1)  showed mild antioxidant activity proved by IC 50 > 250 µg/mL.